A Framework to Support Coalition Formation in the Fourth Party Logistics Supply Chain Coalition - Tatarczak, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The growing diversity of programmes concerning the solutions associated with the fourth party supply chain operations, the increasing pressure to optimise all resources and capabilities, as well as the continually increasing integration of different types of technologies are the driving force in the establishment of fourth party logistics supply chain coalition. Choosing the most rational and practical cost allocation mechanism in the fourth party logistics supply chain coalition, with the aim of reducing the overall operating costs, is the main condition ensuring companies’ motivation to participate in collaboration. This paper addresses the concepts from the game theory combined with multi‑criteria problems in order to introduce a realisable profit distribution mechanism, with the potential to establish practical collaborations among companies. The aim is to achieve the best conditions for collaboration. Case studies are used to demonstrate the utility of the framework.